A Critique of the English Book for 8th Graders Entitled Prospect 2 in Terms of its Cultural Aspects - Reza Taherkhani; Fateme Mottaghi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Globalization has led to changes in the conceptual meaning of culture, one of which is the perception of people towards language in EFL contexts. Critical evaluation of teaching materials is a vital step in improving the status of the books, especially for the future. Therefore, the current study aims to evaluate the English book entitled «Prospect 2» in terms of its cultural aspects. This newly-published book is used to teach English for 8th graders in Iran. In this study, experienced English teachers in Hamedan were interviewed, using Kilickaya's (2004) questions. The results were qualitatively analyzed using Dörnyei's (2007) model. The results revealed that this book is localized to a considerable degree, and the cultural aspects of the book are about the local culture of Iran. Consequently, considering the interrelationship between language and culture, totally omitting the cultural features of the language would lead to incomplete knowledge of the language students are learning.